Implementation of Simulation Software on Vocational High School Students in Programming and Arduino Microcontroller Subject - Budi, AHS; Juanda, EA; Fauzi, DLN; H, Henny; A., Masek (Journal of Technical Education and Training, 2021)
The purpose of this study is to determine students’ learning performance who underwent simulation software class on the Programming and Arduino Microcontroller Subject. A quasi-experimental study, with pretest and posttest design was implemented. The subject involved 74 vocational high school students (37 in the control group and 37 in the experimental group) have undergone eight weeks of treatment, using conventional and Proteus simulation software. Students’ performance was measured using achievement test; involved cognitive, psychomotor, and affective aspect, which was based on the Bloom’s Taxonomy. The result indicated that students in the experimental group have outperformed their counterpart in the control group in cognitive aspect (81.4 vs 76.24), affective aspect (81.83 vs 76.34) and psychomotor aspect (79.04 vs 70.37). Further analysis using independent t-test, result indicated that the experimental group’s performance has significantly difference from the control group’s performance at all aspects [t(72) = 3.068, p = .004]. In conclusion, simulation software using Proteus has a significant contribution to increase students’ performance in learning. The implication is that, teaching difficult subject involves programming of microcontroller should use simulation software, so that students become more enthusiast, have many choices in experimenting and capable of nurturing creativity. Future study suggested to focus on the effect of simulation software on nurturing specific creativity skills.